2002
DOI: 10.2337/diabetes.51.6.1681
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Impairs Hypothalamo-Pituitary-Adrenal (HPA) Responses to Hypoglycemia, and Insulin Treatment Normalizes HPA but not Epinephrine Responses

Abstract: We recently established that in addition to plasma adrenocorticotrophic hormone (ACTH) and corticosterone, hypothalamic corticotrophin-releasing hormone (CRH) mRNA and hippocampal type 1 glucocorticoid receptor (GR1) mRNA were also upregulated in uncontrolled streptozotocin-induced diabetes. In the current study, control, diabetic, and insulin-treated diabetic rats underwent a hyperinsulinemic-hypoglycemic glucose clamp to evaluate central mechanisms of hypothalamo-pituitary-adrenal (HPA) and counterregulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 63 publications
7
67
1
Order By: Relevance
“…3b). This level of basal insulin is similar to other rodent models of type 1 diabetes such as the Akita mouse [8,38] or the streptozotocininduced diabetic rodent [8,39,40]. Considering that these diabetic animals ran considerably less than what is typically observed in healthy animals of the same age/strain (~2.2 vs 9 km per night) [31], these findings provide strong evidence for the anabolic effect of aerobic type exercise on leucine stimulated protein synthesis in the skeletal muscle of diabetic rat models.…”
Section: Discussionsupporting
confidence: 78%
“…3b). This level of basal insulin is similar to other rodent models of type 1 diabetes such as the Akita mouse [8,38] or the streptozotocininduced diabetic rodent [8,39,40]. Considering that these diabetic animals ran considerably less than what is typically observed in healthy animals of the same age/strain (~2.2 vs 9 km per night) [31], these findings provide strong evidence for the anabolic effect of aerobic type exercise on leucine stimulated protein synthesis in the skeletal muscle of diabetic rat models.…”
Section: Discussionsupporting
confidence: 78%
“…This suggests that the HPA axis response to this challenge remains intact in diabetic subjects and is independent of peripheral autonomic dysfunction. However, it should be noted that subjects in the present study were matched in terms of glycaemic control and all had relatively normal glucose levels at the time of testing, and previous studies have reported that uncontrolled diabetes and acute hyperglycaemia or hypoglycaemia may be associated with altered HPA axis activity [12,23]. Cortisol responses to graded exercise have been shown to be impaired in diabetic subjects with autonomic neuropathy, albeit only at maximum workload [14,24], and it has been suggested that this is due to an impairment in sympathetic afferent impulses [24].…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have therefore examined the integrity of the stress response in people with diabetic autonomic neuropathy. Most of these studies have concentrated on the response to hypoglycaemia, and reduced counter-regulatory hormone responses with impaired sympatho-adrenomedullary (SAM) function are well described [11,12]. Responses to other challenges are more variable [2,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Patients and animals with poorly controlled or uncontrolled diabetes commonly show diurnal hypersecretion of GCs and altered regulation of the HPA axis, with enhanced responses to stressors (Chan et al 2002a,b, Sharma et al 2014. In type 1 diabetes mellitus (DM1) patients, stressrelated adaptation of the HPA axis is impaired, with weaker adrenal overnight responsiveness to endogenous adrenocorticotropic hormone (ACTH) and lower free cortisol concentrations (Sharma et al 2014).…”
Section: Hpa In Diabetesmentioning
confidence: 99%